Investigation of concrete-filled steel composite (CFSC) stub columns with bar stiffeners - Bahrami, Alireza; Wan Badaruzzaman, Wan Hamidon; Osman, Siti Aminah (Journal of Civil Engineering and Management, 2013)
This paper is concerned with the investigation of concrete-filled steel composite (CFSC) stub columns with bar stiffeners. In order to study the behaviour of the columns, the finite element software LUSAS is used to conduct the non-linear analyses. Results from the non-linear finite element analysis and the corresponding experimental test are compared which reveal the reasonable accuracy of the three-dimensional finite element modelling. A special arrangement of bar stiffeners in the columns with various number, spacing and diameters of the bar stiffeners are developed and studied using the non-linear finite element method. Effects of various variables such as different number and spacing of the bar stiffeners and also steel wall thicknesses on the ultimate axial load capacity and ductility of the columns are examined. Moreover, effects of different diameters of the bar stiffeners, concrete compressive strengths and steel yield stresses on the ultimate axial load capacity of the columns are evaluated. It is concluded from the study that the variables significantly influence the behaviour of the columns. The obtained results from the finite element analyses are compared with those predicted values by the design code EC4 and suggested equations of the previous researches.